2014
DOI: 10.1111/mve.12053
|View full text |Cite
|
Sign up to set email alerts
|

Northern fowl mite (Ornithonyssus sylviarum) in Sweden

Abstract: Haematophagous mites were collected from the vent region and plumage of chickens in six hobby flocks of ornamental breeds in Sweden, one of which included turkeys. Soiled vent skin and feathers, dermatitis, hyperkeratosis, skin necroses and ulcers were observed in 12 necropsied birds from two of the flocks. The mites were identified as the northern fowl mite Ornithonyssus sylviarum (Mesostigmata: Macronyssidae). This was supported by sequence analysis of a 642-bp region in the mitochondrial cytochrome oxidase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…The genetic distance value obtained from the analysis of the Kimura-2 parameter (K2P) method shows a range of genetic distance values between 0–1.1% (data not shown), suggesting that our result is in the context of divergences within species. This level of intraspecific variation is similar to that found by other researchers for NFM [61]. The pairwise uncorrected genetic distance (p-distance) approach was used by Jansson et al [61] to estimate sequence variation within the range of 0–2.8%.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The genetic distance value obtained from the analysis of the Kimura-2 parameter (K2P) method shows a range of genetic distance values between 0–1.1% (data not shown), suggesting that our result is in the context of divergences within species. This level of intraspecific variation is similar to that found by other researchers for NFM [61]. The pairwise uncorrected genetic distance (p-distance) approach was used by Jansson et al [61] to estimate sequence variation within the range of 0–2.8%.…”
Section: Discussionsupporting
confidence: 81%
“…This level of intraspecific variation is similar to that found by other researchers for NFM [61]. The pairwise uncorrected genetic distance (p-distance) approach was used by Jansson et al [61] to estimate sequence variation within the range of 0–2.8%. Neighbor-joining and Maximum Likelihood trees generated in this study indicated a close relationship between the Chinese isolates, as expected when compared with the GenBank entries of NFM from Europe/USA etc.…”
Section: Discussionsupporting
confidence: 81%
“…In Europe, O. sylviarum was the most frequent mite in nests of wild birds in Slovakia, Italy and Austria (17)(18)(19). It was occasionally also found in poultry (20), pheasants and canaries in France (21), in ornamental chicken breeds in Sweden (22) and, more recently also in pet birds in Portugal (23), but infestation levels are by far not comparable with those of D. gallinae (24). The reasons for the different infestation patterns between continents remain unclear (21).…”
Section: Discussionmentioning
confidence: 99%
“…TFMs are cosmopolitan in tropical and subtropical countries ( 7 , 9 ). Although the issues caused by NFMs are not uniform across the world, they are included as key pests in the poultry industry in North America, Brazil, Australia, and Asia ( 7 , 10 – 12 ).…”
Section: Introductionmentioning
confidence: 99%